2020
DOI: 10.1002/nop2.583
|View full text |Cite
|
Sign up to set email alerts
|

The gerontological nurse specialist’s core competencies in China: A cross‐sectional study

Abstract: At the end of 2018, there were 249 million people aged 65 years or over in China, accounting for 11.4% of the total population (National Bureau of Statistics, 2018). In China, 74.2% of adults older than 60 years have at least 1 common chronic disease (Cui, Mao, & Wang, 2016). Due to the ageing of their bodily organs, it is difficult for them to maintain their physical and psychological balance (Fried, Ferrucci, Darer, Williamson, & Anderson, 2004). A national survey indicated that 59.2% of older inpatients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…This study is the first large-scale national study to investigate gerontological nurse specialists' core competency level in China. The results of the self-administered questionnaire showed that the core competency level of gerontological nurse specialists in China is at an aboveaverage level, which is slightly greater than our previous survey conducted in a province in western China [20].…”
Section: Status Of the Core Competency Of Gerontological Nurse Specia...contrasting
confidence: 67%
See 2 more Smart Citations
“…This study is the first large-scale national study to investigate gerontological nurse specialists' core competency level in China. The results of the self-administered questionnaire showed that the core competency level of gerontological nurse specialists in China is at an aboveaverage level, which is slightly greater than our previous survey conducted in a province in western China [20].…”
Section: Status Of the Core Competency Of Gerontological Nurse Specia...contrasting
confidence: 67%
“…This study is the first large-scale national study to investigate gerontological nurse specialists’ core competency level in China. The results of the self-administered questionnaire showed that the core competency level of gerontological nurse specialists in China is at an above-average level, which is slightly greater than our previous survey conducted in a province in western China [ 20 ]. The attitude subscale received the highest score among the three subscales, and the scores of the two dimensions it contains (i.e., professional self-identity and learning enthusiasm) ranked in the top three in all dimensions, indicating that gerontological nurse specialists engaged passionately in geriatric nursing work.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Core nursing competence is at the hearth of nursing education and plays a key role in ensuring high‐quality services (Chunlan et al, 2020). There is no consensus on the definition of it.…”
Section: Introductionmentioning
confidence: 99%